The Right to Build the City: Can Community Benefits Agreements Bring Employment Equity to the Construction Sector? - Nugent, James (Labour / Le Travail, 2017)
Though rare in Canada, community benefits agreements (cbas) are now commonly being negotiated by labour-community coalitions in American cities. cbas require "urban revitalization" projects to provide living wages, affordable housing, and access to jobs for marginalized residents. Surprisingly little has been written about cbas within the labour studies literature, and most critiques of cbas correspond with private developments. This case study draws on three years of participatory, action-based fieldwork with a labour-community coalition, called the Toronto Community Benefits Network (hereafter, the Network). Formed in 2013, the Network tried to negotiate the first-ever cba with the Ontario government, linked to the $6.6 billion Eglinton Crosstown Light Rail Transit project in Toronto. The Network won discursive support for cbas from provincial policymakers, but demands for employment equity were met with only an ineffective workplace-development approach. I explain and evaluate the Network's "insider strategy" in relation to political vulnerabilities of the government of Ontario; the Network's efforts to mobilize resources and gain union support; and the changing labour-relations regime governing infrastructure projects in Toronto. I argue that while cbas open a new terrain of struggle for marginalized groups and unions to assert a right to the city, these struggles are being coopted by governments and used as political cover for deepening neoliberal governance.